Tingkat Kemampuan Gerak Motorik Kasar Siswa Kelas IV & V Sekolah Dasar Negeri 1 Gulang Kecamatan Mejobo Kabupaten Kudus (Indonesian Journal for Physical Education and Sport, 2022)
Physical growth and motor development can be influenced by several factors, internally and even externally, in physical growth it is clearly seen that there are differences in motor development as well as differences, this occurs according to the physical activities carried out by students. The problem of this research is to “How big is the gross motoric ability of the upper grade students of SD Negeri 1 Gulang, Mejobo District, Kudus Regency"? This research design uses quantitative descriptive research with test and measurement survey methods. The population of this study was the IV and V graders of SD Negeri 1 Gulang, Mejobo District, Kudus Regency. The IV grade students consist of 15 male students and 19 female students, in the V grade there are 13 male students and 20 female students. The method used in this study is a survey method. Based on the results of the study, it was found that the results of the gross motor skills of grade IV and V grade students of SD Negeri 1 Gulang, Mejobo District, Kudus Regency obtained very good categories of 4%, good at 33%, moderate by 28%, less by 25%, and less once by 9%. Based on these results, it can be concluded that most of the gross motor skills of the IV and V graders of SD Negeri 1 Gulang, Mejobo District, Kudus Regency are categorized as “good”.